Non‐confined long‐standing blood chimerism in a spontaneous monochorionic dizygotic twin pregnancy. Issue 3 (26th November 2019) - Daum, Hagit; Frumkin, Ayala; Meiner, Vardiella; Werner, Marion; Macarov, Michal; Gillis, David; Israel, Shoshana; Abed El Latif, Mahmoud; Meir, Karen; Gielchinsky, Yuval
Abstract : The present study highlights a rare case of monochorionic dizygotic twins with non‐confined blood chimerism presenting excellent outcome after two‐year follow‐up.